PENGARUH LIKUIDITAS TERHADAP HARGA SAHAM DENGAN PROFITABILITAS SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN MANUFAKTUR SEKTOR ANEKA INDUSTRI YANG TERDAFTAR DI BEI PERIODE 2013-2016 - Aditya Fahri Mardian; Fauji Sanusi (Tirtayasa Ekonomika, 2017)
The aim of this research is to investigate effect of the Liquidity (CR) to Stock Price with Profitability (ROA) as an intervening on manufacture company in various industry sector which listed on BEI on 2013-2016 . Type of this research is descriptive and associative by using population of various industry companies which listed on BEI from 2013-2016. The sampling technique used is purposive sampling. The research population data are 42 companies, and obtained a sample of 21 companies.The result of path analysis on sub-structure 1 shows that the variable of Current Ratio has positive influence on Return On Asset with tcount> ttable(3,743 > 1,66388), while path analysis in sub-structure 2 shows that variable of Current Ratio has no effect to stock price with tcount < ttable(-2,029 <1,66388), while Return On Asset has positive influence to stock price with tcount < ttable(6,081 >  1,66388). Based on sobel test we’ll known  that the Return On Asset (ROA) variable can be an intervening variable (mediation) for the relation between Current Ratio (CR) and Stock Price in various industry sectors listed on BEI from 2013-2016, because  indirect effect  bigger that is 0,231492, compared to direct effect that is -0,202. While the analysis to test the level of significance shows that tcount0.3404 smaller than the value of z for the value of α = 0.05 that is 1.98, then this shows insignificant results. So it can be concluded the variable Return On Asset (ROA) is not able to mediate the relation of Current Ratio (CR) on Stock Price